2023
DOI: 10.3390/s23073670
|View full text |Cite
|
Sign up to set email alerts
|

Weed Detection Using Deep Learning: A Systematic Literature Review

Abstract: Weeds are one of the most harmful agricultural pests that have a significant impact on crops. Weeds are responsible for higher production costs due to crop waste and have a significant impact on the global agricultural economy. The importance of this problem has promoted the research community in exploring the use of technology to support farmers in the early detection of weeds. Artificial intelligence (AI) driven image analysis for weed detection and, in particular, machine learning (ML) and deep learning (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…As a consequence, there is an increase in the challenges and time taken to produce detailed precision weed maps (Zou et al 2021). To attend to some of these issues, it has been suggested that the use of specialized models or machine learning techniques can provide further enhancement and detection efficiency (Murad et al 2023). In this respect, a range of techniques have been developed to assist in this area, with some examples including the use of (1) artificial intelligence-based image analysis (Aitkenhead et al 2003; Haq et al 2023); (2) deep learning systems and algorithms (such as artificial neutral networks, convolutional neutral networks, deep neutral networks) (Hasan et al 2021; Murad et al 2023); (3) image processing techniques (including clustering, generative adversarial networks, Hilbert transformation, histograms of gradients, linear iterative, local binary patterns) (Murad et al 2023; Nixon and Aguado 2019); and (4) machine learning systems and algorithms (such as adaptive boosting, artificial neutral networks, decision trees, k-nearest neighbor, and support vector machines) (Murad et al 2023).…”
Section: Weed Detection Methodsmentioning
confidence: 99%
“…As a consequence, there is an increase in the challenges and time taken to produce detailed precision weed maps (Zou et al 2021). To attend to some of these issues, it has been suggested that the use of specialized models or machine learning techniques can provide further enhancement and detection efficiency (Murad et al 2023). In this respect, a range of techniques have been developed to assist in this area, with some examples including the use of (1) artificial intelligence-based image analysis (Aitkenhead et al 2003; Haq et al 2023); (2) deep learning systems and algorithms (such as artificial neutral networks, convolutional neutral networks, deep neutral networks) (Hasan et al 2021; Murad et al 2023); (3) image processing techniques (including clustering, generative adversarial networks, Hilbert transformation, histograms of gradients, linear iterative, local binary patterns) (Murad et al 2023; Nixon and Aguado 2019); and (4) machine learning systems and algorithms (such as adaptive boosting, artificial neutral networks, decision trees, k-nearest neighbor, and support vector machines) (Murad et al 2023).…”
Section: Weed Detection Methodsmentioning
confidence: 99%
“…The researchers have employed the Literature Review writing guidance utilized by (Murad et al, 2023). Three processes, as proposed by , were implemented to ensure the alignment of the acquired and assessed data with the study questions.…”
Section: Methodsmentioning
confidence: 99%
“…Deep Neural Networks (DNNs) extend the complexity, number of connections and hidden layers of Artificial Neural Networks (ANNs). A convolutional neural network (CNN), a type of DNN, assigns learnable weights and biases to different aspects and objects within input images to distinguish and classify objects, such as weeds [1]. Unlike traditional machine learning algorithms that require manual feature selection and classifier choice, deep learning algorithms automatically extract features through self-learning from errors.…”
Section: Learning Algorithmmentioning
confidence: 99%
“…Unlike traditional machine learning algorithms that require manual feature selection and classifier choice, deep learning algorithms automatically extract features through self-learning from errors. This automatic feature extraction sets deep learning apart from the broader field of machine learning [1,92,93]. To train and evaluate a deep CNN model, each input image undergoes a sequence of convolution layers with filters, followed by flattening, pooling layers and fully connected layers.…”
Section: Learning Algorithmmentioning
confidence: 99%
See 1 more Smart Citation